CUSTOMARY INTERNATIONAL HUMANITARIAN LAW AND HUMAN RIGHTS IN ARMED CONFLICTS - Jance, Kristinka; Tiri, Edvana (International Journal of Legal and Social Order, 2024)
International law is derived from both treaty law and customary international law. Treaties are formal written agreements among States that establish specific rules. On the other hand, customary international law is not codified in written form but is based on "a general practice accepted as law". It must be shown that a norm is reflected in state practice and that the international community views it as legally binding in order to prove that it is customary. Rules derived from "a general practice accepted as law" make up customary international law, which exists apart from treaty law. Customary international humanitarian law (IHL) is essential in contemporary armed conflicts because it fills in the legal gaps left by treaty law in both international and non-international conflicts and improves the protections provided to victims.